Low genetic diversity of oval squid, Sepioteuthis cf. lessoniana (Cephalopoda: Loliginidae), in Japanese waters inferred from a mitochondrial DNA non-coding region - Aoki, M. (2014)
10.2984/1534-6188(2008)62[403:LGDOOS]2.0.CO;2